Applications of complementary therapies during rehabilitation for individuals with traumatic Spinal Cord Injury: Findings from the SCIRehab Project. (3rd September 2019) - Taylor, Sally M.; Cheung, Elaine O.; Sun, Ruichen; Grote, Veronika; Marchlewski, Anthony; Addington, Elizabeth L.
Abstract : Objective: Evaluate the use of complementary therapies during rehabilitation for patients with traumatic spinal cord injury (SCI). Design: Secondary analyses were conducted to identify the use and associated outcomes of complementary therapies provided by occupational therapists (OTs) and physical therapists (PTs) during rehabilitation from a public dataset. Setting: Inpatient rehabilitation. Participants: A public dataset composed of 1376 patients with SCI that were enrolled in a five-year, multi-center investigation, the SCIRehab Project. Secondary analyses focused on a subset of 93 patients (47 who received complementary therapy during treatment and 46 case-matched controls who received no complementary therapy). Interventions: OTs and PTs recorded use of complementary therapies during sessions, including yoga, Pilates, tai chi, aromatherapy, relaxation techniques, imagery and other. Outcome Measures: Pain interference, pain severity, mobility, and social integration. Results: Three percent of participants received any complementary therapies. Patients who received complementary therapies showed greater reductions in pain severity from 6 months to 12 months relative to matched controls. Furthermore, the amount of time that patients received complementary therapies during physical therapy sessions was associated with reduced pain interference at 6 months and with reduced pain severity at the 6-month and 12-month follow-ups. Complementary therapy use was not associated with mobility or social integration. Conclusion: The current study provides preliminary evidence documenting the limited use of complementary therapies in rehabilitation settings and highlights the opportunity for further research, particularly regarding pain-related outcomes.